2020
DOI: 10.1007/978-3-030-51916-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium Presence and Functions in Microbiomes of Non-leguminous Plants

Abstract: The Springer series Soil Biology publishes topical volumes in the fields of microbiology, environmental sciences, plant sciences, biotechnology, biochemistry, microbial ecology, mycology and agricultural sciences.Special emphasis is placed on methodological chapters or volumes. This includes coverage of new molecular techniques relevant to soil biology research or to monitoring and assessing soil quality as well as advanced biotechnological applications. Leading international authorities with a background in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1,216 publications
(1,712 reference statements)
0
4
0
1
Order By: Relevance
“…Rhizobium can be found in the rhizosphere, endosphere, and phyllosphere of non-leguminous crops, according to D‫ם‬ez M‫י‬ndez and Men‫י‬ndez. 57 Regardless, cotton Rhizobium inoculation has been seldom documented in the literature. Romero-Perdomo et al 58 found that Rhizobium was the sole bacterium that positively impacted cotton development in soils deficient in phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizobium can be found in the rhizosphere, endosphere, and phyllosphere of non-leguminous crops, according to D‫ם‬ez M‫י‬ndez and Men‫י‬ndez. 57 Regardless, cotton Rhizobium inoculation has been seldom documented in the literature. Romero-Perdomo et al 58 found that Rhizobium was the sole bacterium that positively impacted cotton development in soils deficient in phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…6 and 7). Rhizobium, an important genre upregulated in the tolerant species, is a wellknown nitrogen-xer [49] and explains the high growth rate of G. arboreum than G, hirsutum. Methylophilus, another bacterial genre upregulated in G. arboreum, has been documented to play a signi cant role in plant growth promotion by utilizing reduced carbon compounds [50], along with Rhizobiales, that are extensively researched partners of plants, often offering valuable contributions to their hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizobium bacteria form a symbiotic relationship with roots of legume crop that results in N fixation, as well as increased uptake of P and macronutrients by the plant and reduced impact of stress factors ( Nadeem et al., 2009 ). Symbiotic bacteria may also promote plant growth by supplying additional N through atmospheric N 2 fixation, producing phytohormones (auxins, cytokinins, and gibberellins), and releasing anti-microbial molecules to shield crops from diseases ( Afkhami et al., 2021 ; Akinola and Babalola, 2020 ; Barka et al., 2016 ; Díez-Méndez and Menéndez, 2021 ; Flores-Félix et al., 2019 ; Khan, 2005 ; Lindstrom and Mousavi, 2019 ; Menendez and Paço, 2020 ; Mupambwa et al., 2018 ; Murali et al., 2021 ; Siqueira et al., 2020 ). In the past, farmers have widely used earthworms and organic fertilizers to boost soil productivity ( Rashid et al., 2013 , 2014a , 2014b , 2016 ; Shah et al., 2013 ), and these practices have proven to be beneficial to agro-ecosystems.…”
Section: Importance Of Microbial Community To Soil Fertility and Sustainabilitymentioning
confidence: 99%